The Utilization of Seed Priming as a Tool to Overcome Salt and Drought Stresses: Is Still a Long Way to Go? - Cinzia Forni; Ilaria Borromeo (Seeds, 2023)
Abiotic stresses, sometimes due to dramatic environmental changes, such as sudden and heavy rainfalls, or drought, increasing temperatures or soil salinization, deeply affect the growth and yield of plants. Progress in terms of improving the abiotic stress tolerance of plants can be obtained via classical breeding and genetic engineering, which can be slow, or by practice, such as acclimation and seed priming. The latter can improve seedling performance, and it can be considered a short-term approach. Seed priming with different agents and biopriming may offer the possibility to improve stress tolerance, even though its beneficial effect depends on crop species, dose, and time of application. The aim of this review is to highlight some of the current research trends that may ultimately lead to strategies for stress-proofing crop species. The focus is on those abiotic stresses, e.g., drought and soil salinity, that are most often associated with climate change and poor agricultural practices and those crops that are most important for human nutrition. Comments are provided on the challenges and pros and cons of this methodology.